Eschatology, Ontology, and Human Action - Webster, John (Toronto journal of theology, 1991)
In this paper, I will attempt to isolate a feature of the usus theologicus of Christian language about human agency by drawing attention to its eschatological component. Explication of Christian eschatological convictions, I suggest, demands that theology fashion a set of ontological categories about created being which are oriented towards 'the new', towards that which the creation becomes by virtue of the regenerative action of God in Christ through the power of the Spirit. Such an ontology, in tum, is bound up with a particular understanding of the range and significance of human action. These ontological and anthropological proposals are necessary, I believe, if we are properly to construe 'doing' according to its theological grammar.